Binding mode–guided development of high-performance antibodies targeting site-specific posttranslational modifications - Mariapia Riso; Rohan N. Shah; Akiko Koide; Alexander J. Ruthenburg; Shohei Koide; Takamitsu Hattori (Proceedings of the National Academy of Sciences, 2025)
Posttranslational modifications (PTMs) of proteins play critical roles in regulating many cellular events. Antibodies targeting site-specific PTMs are essential tools for detecting and enriching PTMs at sites of interest. However, fundamental difficulties in molecular recognition of both PTM and surrounding peptide sequence have hindered the efficient generation of highly sequence-specific anti-PTM antibodies. Furthermore, the widespread use of potentially inconsistent, nonrenewable, and molecularly undefined antibodies presents experimental challenges thought to contribute to the reproducibility problem in biomedical research. In this study, we describe the binding mode-guided development of a platform that efficiently generates potent and selective recombinant antibodies to PTMs that are molecularly defined and renewable. Our platform is built on our previous discovery of an unconventional binding mode of anti-PTM antibodies, antigen clasping, where two antigen binding sites cooperatively sandwich a single antigen, creating extensive interactions with the antigen and leading to high selectivity and potency. We designed the platform that generates clasping antibodies with two distinct binding units, resulting in efficient generation of antibodies to a set of trimethylated histone H3 with high levels of specificity and affinity. Performance comparison in chromatin immunoprecipitation, a common application in epigenomics, revealed that a clasping antibody to trimethylated histone H3 at lysine 27 exhibited superior specificity to a widely used conventional antibody and captured symmetric and asymmetric nucleosomes in a less biased manner. We further generated clasping antibodies to phosphotyrosine antigens by using the same principle. These results suggest the broad applicability of our platform to generating high-performance clasping antibodies to diverse PTMs.